The sugar smart diet : stop cravings and lose weight while still enjoying the sweets you love! - Alexander, Anne (Anne Adele) (Rodale, 2014)
A thirty-day guide to eliminating dietary sugar identifies its emotional and physiological consequences, reveals unexpected sources of sugar, and provides dozens of recipes.